Measures and Prospects of Technology Transfer Processes Improvement in Russian Economy (Due to An Expert Study Materials) - Olga PYATAEVA; Alexander ANISIMOV; Sergey EROKHIN; Lilia MATRAEVA; Artyom GAVRILYUK (Communications of International Proceedings, 2021)
The current structure of Russian economy make possible having specific conditions that simple technological intermediation between a technology developer and its recipient, which is handled by most domestic entities, is failure. It seems that the list of reasons for this (including by industry) can be supplemented; therefore, the authors of this article carried out an expert study «Transfer of technologies: prospects of development of innovative infrastructure of the Russian Federation» for entrepreneurs, developers of innovative ideas working on innovations. The results of the study is listed below in this article.
Keywords: Technology Transfer; Expert Study; Developers Of Innovative Ideas; Innovation Technologies; Innovation Process; Russian Economy.